2008
DOI: 10.1007/s00425-008-0733-1
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus possesses an expanded set of polygalacturonase inhibitor protein genes that are differentially regulated in response to Sclerotinia sclerotiorum infection, wounding and defense hormone treatment

Abstract: Most plants encode a limited set of polygalacturonase inhibitor (PGIP) genes that may be involved in aspects of plant development, but more importantly in the inactivation of polygalacturonases (PG) secreted by pathogens. Previously, we characterized two Brassica napus PGIP genes, BnPgip1 and BnPgip2, which were differentially expressed in response to pathogen infection and wounding. Here we report that the B. napus genome encodes a set of at least 16 PGIP genes that are similar to BnPgip1 or BnPgip2. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Abiotic stresses, such as SA, low temperature, jasmonate (JA), and oligogalacturonides, can also induce the PGIP expression (Li et al 2003;Hegedus et al 2008). For example, in Arabidopsis, cold induces the expression of AtPGIP1 but not AtPGIP2 (Ferrari et al 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Abiotic stresses, such as SA, low temperature, jasmonate (JA), and oligogalacturonides, can also induce the PGIP expression (Li et al 2003;Hegedus et al 2008). For example, in Arabidopsis, cold induces the expression of AtPGIP1 but not AtPGIP2 (Ferrari et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…PGs degrade plant cell wall, which make other hydrolyzation enzymes to degrade cell wall more easily (Karr and Albersheim 1970). Poylgalacturonase-inhibiting proteins (PGIPs) are cell wall proteins that inhibit the activity of fungal PGs and retard the invasion of plant tissues by pathogens (Ferrari et al 2006;Spadoni et al 2006;Joubert et al 2007;Cheng et al 2008;Hegedus et al 2008;Janni et al 2008;Protsenko et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Genes that encode these proteins have been characterized in both monocotyledons and dicotyledons. Genomic analyses have shown that PGIP genes may exist as a single gene, for example in diploid wheat species (Di Giovanni et al, 2008), or are organized into gene families whose members are tandemarranged and may vary from two, as in Arabidopsis thaliana (Ferrari et al, 2003), to 16, as in Brassica napus (Hegedus et al, 2008). The overexpression of PGIP genes in transgenic plants such as wheat, tomato, tobacco, and A. thaliana limits fungal colonization (Powell et al, 2000;Ferrari et al, 2003;Manfredini et al, 2005;Janni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Ferrari et al, 2003) and Brassica napus L. (Li et al, 2003;Hegedus et al, 2008). In P. vulgaris, four genes code for proteins that show sequence variation from 3 to 24%.…”
Section: Introductionmentioning
confidence: 99%